P215 Measuring occupational health and safety vulnerability: what can it add to our understanding of injury risk and primary prevention activities. (1st September 2016) - Smith, Peter; Lay, Morgan; Saunders, Ron; LaMontagne, Anthony; Breslin, Curtis; Tompa, Emile
Abstract : Vulnerability is a commonly used, but not well defined, metric in the prevention system. This presentation will describe a recently developed measure to define OH&S vulnerability. In this presentation we will describe the development of a new measure of occupational health and safety (OH&S) vulnerability. The purpose of this measure was to allow the identification of workers at increased risk of injury, and to enable to monitoring and surveillance of OH&S vulnerability in the labour market. This measure conceives of OHS vulnerability as a combination of exposure to hazards in combination with the presence of one of three other dimensions that increase injury risk. These three other dimensions are: inadequate protection from workplace policies and practices, low worker awareness of OHS rights and responsibilities, and low worker empowerment to take part in making work safer. Using a sample of approximately 2, 000 workers in Ontario and British Columbia we have demonstrated that although younger workers, temporary workers and workers in small businesses were vulnerable, they were vulnerable in different ways. Temporary workers were more likely to experience vulnerability in relation to hazards and lack of awareness or empowerment, while workers in small businesses were more likely to experience vulnerability related to workplace policies and procedures. In a second study, we have found the impacts of the different dimensions of vulnerability are super-additive (i.e. the impacts of the combination of dimensions of vulnerability is greater than their impact in isolation), on risk of injury and worrying about getting injured at work. Taken together, this new measure of vulnerability can be used to better understand how different workplace contexts place workers at increased risk of injury, thus informing primary prevention at the workplace and system levels.